Carbon‐Based Radar Absorbing Materials toward Stealth Technologies - Kim, Seong‐Hwang; Lee, Seul‐Yi; Zhang, Yali; Park, Soo‐Jin; Gu, Junwei (Advanced science, 2023)
Stealth technology is used to enhance the survival of military equipment in the field of military surveillance, as it utilizes a combination of techniques to render itself undetectable by enemy radar systems. Radar absorbing materials (RAMs) are specialized materials used to reduce the reflection (or absorption) of radar signals to provide stealth capability, which is a core component of passive countermeasures in military applications. The properties of RAMs can be optimized by adjusting their composition, microstructure, and surface geometry. Carbon‐based materials present a promising approach for the fabrication of ultrathin, versatile, and high‐performance RAMs due to their large specific surface area, lightweight, excellent dielectric properties, high electrical conductivity, and stability under harsh conditions. This review begins with a brief history of stealth technology and an introduction to electromagnetic waves, radar systems, and radar absorbing materials. This is followed by a discussion of recent research progress in carbon‐based RAMs, including carbon blacks, carbon fibers, carbon nanotubes, graphite, graphene, and MXene, along with an in‐depth examination of the principles and strategies on electromagnetic attenuation characteristics. Hope this review will offer fresh perspectives on the design and fabrication of carbon‐based RAMs, thereby fostering a deeper fundamental understanding and promoting practical applications.